Detection and Control Bacteria Cause Grain Rot Burkholderia glumae on Rice - Syahri Syahri; Renny Utami Somantri; Priatna Sasmita (Universitas Gadjah Mada, 2019)
Burkholderia glumae, before mid-2018, is categorized as plant quarantine pest A2 Group 1 that its existence has been detected in Indonesia. B. glumae has been known to spread in the central production of rice in Java, Sumatra, Borneo dan Sulawesi. This review aimed to explain the strategies for B. glumae detection through its characteristics and to prevent the divergence of this bacterium in Indonesia. The previous studies reported that the bacteria could reduce yield up to 75% and caused the decrease of weight-grain or the increase of empty grain. The disease intensity is affected by environmental and physiological factors such as warm temperature at nighttime and high rainfall intensity. The optimum temperature for the development of the disease is 30–35°C. Moreover, the pathogen could survive at a temperature of 41°C. The tropical area of 32-36°C are suitable for B. glumae. Recently, the effective control of the disease in the field has not been found yet. Meanwhile, early detection of the disease is not yet determined, even though it is necessary to prevent its spread in rice cultivation in Indonesia. Detection of the disease by Agricultural Quarantine Agency as a frontline is needed to check the entry of the disease carried by the import activities of the seed. Detection in the suspected field by protection institutes through frequent surveillance in central production areas of rice should be considered as an important task.. The effective techniques to prevent B. glumae are the use of resistant varieties, the practice of seed treatments (using antibacterial, bactericide, heat treatment or plant extract), and the application of oxolinic acid to the crops.